Participant-Reference Shifts in Zech. 1:1-6: An Assessment of Diachronic and Synchronic Approaches - Jensen, Christian Højgaard (HIPHIL Novum, 2016)
Using Zech. 1:1-6 as a case-study, diachronic and synchronic methodologies are discussed in terms of their ability to explain participant-reference shifts in the Hebrew Bible. It is suggested that the analysis should begin with a linguistic investigation of the form and function of the participant-references in their literary context. Accordingly, building upon the participant tracking that Eep Talstra has done in Zech. 1:1-6, a linguistic framework is outlined in order to assess various interpretations and translations. Patterns of participant-reference shifts observed in other parts of the Hebrew Bible are included to suggest rhetorical functions of the participant shifts. It is concluded that it is necessary to combine the linguistic analysis with a discourse theory that treats the text as an act of communication. In particular, Role and Reference Grammar is suggested as a beneficial starting point for further research.